Characterization of the complete mitochondrial genome of cape elephant shrew, Elephantulus edwardii - Chang-Zhong Liu; Lei Wang; Xiao-Jing Xia; Jin-Qing Jiang (Mitochondrial DNA. Part B. Resources, 2018)
In this study, the complete mitochondrial genome of cape elephant shrew, Elephantulus edwardii, was determined through sequencing of PCR fragments. The complete mitochondrial genome of E. edwardii was 16,552 bp in length and and encoded 13 protein-coding genes, 22 transfer RNA (tRNA) genes, and two ribosomal RNA genes. The overall nucleotide composition is: 32.7% A, 29.5% T, 25.0% C, and 12.9% G, with a total G+C content of 37.9%. By phylogenetic analysis using Bayesian method, E. edwardii showed the closest relationship with another Elephantulus speceis (Genbank accession: AB096867.1).